2018
DOI: 10.3390/toxins10100417
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Analysis for Assessing the Early Response to DSP Toxins in Mytilus galloprovincialis Digestive Gland and Gill

Abstract: The harmful effects of diarrhetic shellfish poisoning (DSP) toxins on mammalian cell lines have been widely assessed. Studies in bivalves suggest that mussels display a resistance to the cytogenotoxic effects of DSP toxins. Further, it seems that the bigger the exposure, the more resistant mussels become. To elucidate the early genetic response of mussels against these toxins, the digestive gland and the gill transcriptomes of Mytilus galloprovincialis after Prorocentrum lima exposure (100,000 cells/L, 48 h) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 72 publications
0
15
1
Order By: Relevance
“…All the profile dataset of four omics were downloaded from the UCSC Xena database. Briefly, level 3 gene expression profiles with 20,530 gene features recorded in the UCSC Xena database were experimentally generated using the Illumina HiSeq 2000 RNA sequencing platform (Prego-Faraldo et al, 2018) from the University of North Carolina TCGA genome characterization center. The stored exon expression profiles were generated using the same platform as the gene expression profiles, with 239,322 exon features.…”
Section: Data Sourcementioning
confidence: 99%
“…All the profile dataset of four omics were downloaded from the UCSC Xena database. Briefly, level 3 gene expression profiles with 20,530 gene features recorded in the UCSC Xena database were experimentally generated using the Illumina HiSeq 2000 RNA sequencing platform (Prego-Faraldo et al, 2018) from the University of North Carolina TCGA genome characterization center. The stored exon expression profiles were generated using the same platform as the gene expression profiles, with 239,322 exon features.…”
Section: Data Sourcementioning
confidence: 99%
“…Interestingly, a number of transcripts associated to OA toxicity like the specific targets PP1 and PP2A and multi-xenobiotic resistance proteins failed to show significant changes in expression [ 81 ]. In a similar study, Prego-Faraldo et al (2018) [ 82 ] assessed the early response (48 h) of the same mussel to P. lima (1 × 10 5 cell L −1 ) using a RNA-Seq analysis showing, in this turn, a higher number of DGEs in gills compared to digestive gland. These included transcripts involved in defense, immunity and metabolism, and since many of them have been described as making part of a common cellular stress response of bivalves to other stimuli [ 83 ], it is suggested that mussel’s resistance mechanism to DSTs is to some extent unspecific [ 82 ].…”
Section: Ecotoxicological Effects Of Dstsmentioning
confidence: 99%
“…In a similar study, Prego-Faraldo et al (2018) [ 82 ] assessed the early response (48 h) of the same mussel to P. lima (1 × 10 5 cell L −1 ) using a RNA-Seq analysis showing, in this turn, a higher number of DGEs in gills compared to digestive gland. These included transcripts involved in defense, immunity and metabolism, and since many of them have been described as making part of a common cellular stress response of bivalves to other stimuli [ 83 ], it is suggested that mussel’s resistance mechanism to DSTs is to some extent unspecific [ 82 ]. Furthermore, results also seem to support a key role of the extracellular exosome and respiratory chain in both mussel tissues in the response to DSTs.…”
Section: Ecotoxicological Effects Of Dstsmentioning
confidence: 99%
See 2 more Smart Citations